2015
DOI: 10.1007/s00406-015-0588-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MAPK/ERK signaling blocks hippocampal neurogenesis and impairs cognitive performance in prenatally infected neonatal rats

Abstract: Hippocampus endogenous neurogenesis has been postulated to play a favorable role in brain restoration after injury. However, the underlying molecular mechanisms have been insufficiently deciphered. Here we investigated the potential regulatory capacity of MAPK/ERK signaling on neurogenesis and the associated cognitive performance in prenatally infected neonatal rats. From our data, intrauterine infection could induce hippocampal neuronal apoptosis and promote endogenous repair by evoking neural stem cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…GSB-214 activated the PI3K/AKT pathway only, which is mainly associated with neuroprotection 10. GSB-106 activated the MAP-kinase pathway along with the PI3K/AKT pathway, with the former playing a pivotal role in the mechanisms of neurogenesis and neuroplasticity 11,12. Previously, we reported that the dimeric dipeptide mimetic of NGF loop 4, which selectively activates the PI3K/AKT pathway, reduced brain infarct volume by approximately 18% in a model of MCAO in rats 21.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSB-214 activated the PI3K/AKT pathway only, which is mainly associated with neuroprotection 10. GSB-106 activated the MAP-kinase pathway along with the PI3K/AKT pathway, with the former playing a pivotal role in the mechanisms of neurogenesis and neuroplasticity 11,12. Previously, we reported that the dimeric dipeptide mimetic of NGF loop 4, which selectively activates the PI3K/AKT pathway, reduced brain infarct volume by approximately 18% in a model of MCAO in rats 21.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway has been associated mainly with neuroprotection 10. The MAPK pathway is also involved in neuroprotection and plays a pivotal role in the mechanisms of neurogenesis and neuroplasticity 11,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenesis which has been shown to be involved in cognitive impairment and depression in humans and in a variety of rodent models, is a function of serotonergic regulation and may affect the response to antidepressants in both cognitive and affective behavioral domains (Adeosun et al, 2014;Alenina and Klempin, 2015;Anacker, 2014;Biscaro et al, 2012;Braun and Jessberger, 2014;Chadwick et al, 2011;Cho et al, 2015;Dimitrov et al, 2014;Gundersen et al, 2013;Hill et al, 2015;Jiang et al, 2015;Lin and Wang, 2014;Mendez-David et al, 2013;Morais et al, 2014;O'Leary and Cryan, 2014;Parihar et al, 2013;Pereira Dias et al, 2014;Ransome et al, 2012;Rotheneichner et al, 2014;Schoenfeld and Cameron, 2015;Seib et al, 2013;Serafini et al, 2014;Shetty, 2014;Suarez-Pereira et al, 2015;Yau et al, 2014). In young adult mice, antidepressants increase stem cell proliferation (Hodes et al, 2010;Santarelli et al, 2003;Tanti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors by which the expression of growth factors is rigorously modulated receive great interest. CREB is a transcription factor that acts as a central regulator of NSPCs proliferation and survival, and common final phosphorylation substrate for several kinasemediated signaling pathways, including the cAMP/Protein kinase A pathway, calcium-calmodulin-m ediated NMDA receptor signaling, phosphatidylinositol 3-kinase (PI3K)/Akt pathway, as well as MAP kinase signaling (Peltier et al, 2007;Mantamadiotis et al, 2012;Faigle and Song, 2013;Jiang et al, 2015). Administration of pharmacological CREB activator (Nakagawa et al, 2002) or retroviral vector-mediated over-expression of wild-type CREB (Peltier et al, 2007) increases adult hippocampus neural progenitor proliferation, whereas dominant negative CREB (Peltier et al, 2007) or conditional gene knockout of CREB (Dworkin et al, 2009) exerts an opposed influence.…”
Section: Discussionmentioning
confidence: 99%